Evaluation of information literacy status among medical students at Shiraz University of Medical Sciences - LEILA BAZRAFKAN; ALI ASGHAR HAYAT; KARIM ABBASI; AGHDAS BAZRAFKAN; AZADEH ROHALAMINI; MOZHGAN FARDID (Journal of Advances in Medical Education and Professionalism, 2017)
Introduction: The information literacy status and the use of information technology among students in the globalization age of course plans are very momentous. This study aimed to evaluate the information literacy status and use of information technology among medical students of Shiraz University of Medical Sciences in 2013. Methods: This was a descriptive-analytical study with crosssectional method. The study population consisted of all medical students (physiopathology, externship and internship) studying at Shiraz University of Medical Sciences. The sample size (n=310) was selected by systematic random sampling. The tool of data gathering was LASSI questionnaire (assigned by America research association) with 48 closed items in five-point LIKERT scale. The questionnaire included two distinct parts of demographic questions and the information literacy skills based on the standards of information literacy capacities for academic education. The content validity was acquired by professors’ and experts’ comments. The reliability was also calculated by Cronbach’s alpha (0.85). Data were analyzed in both descriptive (frequency- mean) and analytical level (t-test, analysis of variance) using SPSS 14 software. Results: 60.3% of the participants were females, and the remaining (29.7%) were males. The mean score of information literacy and its five subgroups among the students weren’t at a desirable level. The mean scores of information literacy for educational grades from the highest to lowest belonged to the internship, physiopathology and externship. The results showed that the highest average was related to the effective access ability to information among interns (9.27±3.57) and the lowest one was related to the ability of understanding legal and economical cases related with using information among externs (3.11±1.32). The results of ANOVA showed that there wasn’t a significant difference between educational grades and information literacy. Finally, the result of independent t-test did not show a significant difference between the two genders in information literacy. Conclusion: Regarding the importance of information literacy for medical students and undesirable status of information literacy among students, the current educational plans will need to be revised.